Jigsaw Technique in Learning Physics and Problem-solving Dimensions of Senior High School Students - Giovanni Pelobillo (Philippine Association of Institutions for Research, Inc., 2018)
Physics was perceived as a difficult subject with in dire need for cooperative learning and problem-solving skills rubric modified from Jennifer Docktor, namely, useful description, physics approach, the specific application of physics, mathematical procedures, and logical progression. This study aimed to determine and describe the effectiveness of jigsaw technique in physics learning and problem-solving skills which employed pretest-posttest and quasi-experimental research design with a 95% confidence level. There were two groups included in the study as control and the experimental group which received jigsaw technique and traditional teaching respectively as treatment. Independent samples t-test results showed the use of jigsaw technique as cooperative learning has a statistical difference on the post-test and post-rubric scores against the control group with the large effect size in which the students showed a proficient performance in learning physics and problem-solving skills with the common use of useful description and physics approach. There is no significant difference on the pre-test and pre-rubric scores between the control and experimental group with the p-value of 0.772 and 0.019. Moreover, this study revealed that the experimental group struggled with mathematical procedures and logical progression posting low percentage gain. Overall this study concludes that students' exposure to jigsaw technique improved physics learning.